Juventude e educação técnica: a experiência na formação de jovens trabalhadores do Colégio Estadual Prof. Horacio Macedo /CEFET-RJ - Simões, Carlos Artexes (2008)
At the beginning of the 21st century, Brazil faces huge difficulties in meeting the needs of its population, especially the young people basic rights to quality education for all and nonalienated work. Informal work and underemployment prevail in production relations and the quantitative expansion of the school system has been characterized as a degrading offering to popular sectors. A large contingent of young people has abandoned their perspective on study and work. Some educational proposals seek if a counterpoint to this social reality, seen here as a tension between the structure of a capitalist system and the strategy used by the social artists, and, in particular, the working young people. This dissertation seeks to unveil the possibility of using technical formation to the poor young people in their social rising and personal and collective development. It has the objective of analyzing the experience of young people coming from state schools, in their educational trajectories and insertion into work after graduating and participating in the educational program of secondary education offered at Colégio Estadual Prof. Horacio Macedo, in articulation with the technical education of Centro Federal de Educação Tecnológica Celso Suckow da Fonseca (CEFET-RJ). This study deals with a case that emphasizes originalities and peculiarities of the experience of young people from popular layers of society, that finished secondary education and had the opportunity to attend technical education at CEFET-RJ, but with a comprehensive perspective of the understanding of the theme related to the issue of the young people formation and their relation with work.